2019
DOI: 10.3390/environments6010004
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Health Effects and Soundscape Analysis as New Mitigation Actions Concerning the Aircraft Noise Impact in Small- and Middle-Size Urban Areas in Greece

Abstract: In 2013 and 2014, two main International Airports in Greece were evaluated through the European directive on noise environment 2002/49/EC: “Nikos Kazantzakis” International Airport of Heraklion Crete and “Ioannis—Kapodistrias” International Airport in Corfu, both located in highly touristic areas of Greece. Acoustic measurement’s campaign, environmental noise mapping simulations and population exposure to noise were implemented in order to produce a complete Strategic Noise Map. Correlated to this acoustic app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In particular, long-term exposure to environmental noise affects cardiovascular system and can play a role in the development of manifest diseases such as hypertension, ischemic heart disease and stroke [29]. Environmental noise in airport settings represent a well-known risk factor for workers employed in airport activity and for inhabitants who live nearby airports [30]. Several studies reported an association between noise exposure generated from aircraft traffic and some effects on the cardiovascular system, such as an increased risk of cardiovascular diseases (myocardial infarction and stroke) and an increased risk of hospitalization for cardiovascular diseases for subjects living in the neighbouring areas of a civil airport [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, long-term exposure to environmental noise affects cardiovascular system and can play a role in the development of manifest diseases such as hypertension, ischemic heart disease and stroke [29]. Environmental noise in airport settings represent a well-known risk factor for workers employed in airport activity and for inhabitants who live nearby airports [30]. Several studies reported an association between noise exposure generated from aircraft traffic and some effects on the cardiovascular system, such as an increased risk of cardiovascular diseases (myocardial infarction and stroke) and an increased risk of hospitalization for cardiovascular diseases for subjects living in the neighbouring areas of a civil airport [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the influence at the inhabitants' acoustic comfort regarding aircraft operation is proven to be an important factor in the evaluation of the impact to local population [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…As Margaritis and Kang (2017) highlighted, noise pollution is significantly influenced by urban design, urban density, urban morphology, street distribution, street environment, and urban land use. Gerolymatou et al (2019) also noted that the design of public spaces and activities hosted within the neighbourhood buildings can have a significant acoustic impact on the sound comfort experienced by the residents.…”
Section: Implications From the Effect Of Land Use And Landscape On So...mentioning
confidence: 99%